The Czech National Bank’s monetary policy since 2008 and its (un)intended consequences in the long run - Wawrosz, Petr; Křížek, David (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: The article aims to show that the monetary policy of the Czech National Bank (CNB) between 2008 and 2021 was mainly expansionary, especially due to foreign exchange interviews realized by the bank from November 2013 to April 2017 to prevent CZK appreciation. The policy contributes to higher Czech inflation from the first half of 2022 to the first half of 2024. Methodology: The relationships between monetary aggregates (M1, M2 and M3 and the stock of CNB foreign exchange reserves) and between the reserves, money stock and inflation are statistically investigated. The article uses, among others, the Augmented Dickey-Fuller test and F-test of the ANOVA procedure. It also discusses how household consumption and government expenditure, mainly in the period since 2021, contributed to the Czech inflation. Results: The study revealed the strong dependence of the development of Czech monetary aggregates (both M1 and M2, and M3) on the development of the stock of the CNB’s foreign exchange reserves. It further proved, using the quantitative equation of money, that the growth of Czech money stock, although partly offset by the negative value of Czech money velocity growth rate, led to the increase in Czech inflation numbers. Originality/value: The article emphasizes that although monetary policy, including forecasts of eco-nomic development, focuses on a period that usually does not exceed two years from taking a specific monetary policy step (e.g. a decision by the central bank to increase or decrease rates) or from the publication of a forecast, i.e. the monetary policy horizon covers up to two years, especially if an expansionary monetary policy is carried out for a longer period. Thus, a central bank should evaluate such a policy, including the issue of how the growth of the value of monetary aggregates can influence inflation values behind the monetary policy horizon. The article further proved that money is neutral in the long run and money growth higher than the growth rate of real GDP must inevitably lead to an increase in inflation. Thus, the CNB expansionary monetary policy had some (un)intended consequences and the central bank faced in the period 2022-2024 higher inflation.
Argumenta Oeconomica, 2025, Nr 1 (54), s. 204-224
Keywords: foreign exchange intervention; quantitative theory of money; inflation; monetary aggregates; Czech National Bank; Czech Republic; Czechia